Pengaruh Mekanisme Tata Kelola Perusahaan yang Baik, Pengungkapan Tanggung Jawab Sosial Perusahaan, dan Pengembalian atas Penggunaan Asset Terhadap Nilai Perusahaan - Setiarini, Anggi Adinda; Sulistyo, Sulistyo; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
This study aims to determine the effect of good corporate governance mechanisms, corporate social responsibility disclosure, and return on assets to firm value. The population used in this study is a publicly listed banking company listed on the Indonesia Stock Exchange in the 2014-2015 period and the sample determination method used was purposive judgment sampling. Samples obtained were 42 companies. Data analysis techniques used are descriptive analysis, classic assumption test, multiple linear regression test, and hypothesis testing. This study found that simultaneously the mechanism of good corporate governance, corporate social responsibility disclosure, and return on assets affect the value of the company. Partially, this study found that the mechanism of good corporate governance that was proxied by the board of directors (DD), board of commissioners (DK), managerial ownership (KM), return on assets (ROA) influenced the company value, while institutional ownership (IC) and corporate social responsibility (CSR) does not affect the company's value